2000
DOI: 10.1080/01652176.2000.9695052
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous medetomidine on pupil size and intraocular pressure in normotensive dogs

Abstract: SUMMARYMedetomidine, a highly specific a-2 adrenergic agonist, has been demonstrated to lower intraocular pressure (lOP) in rabbits and cats when applied topically. The purpose of this study was to assess the influence of intravenously injected medetomidine on the pupil size (PS) and the IOP of non glaucomatous dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 3 publications
6
45
3
1
Order By: Relevance
“…Nevertheless, in the present study, a significant decrease in PS was observed when compared with the insignificant changes in IOP. This result suggests that the changes in PS were not related to IOP, which is in agreement with the hypotheses and findings presented by Kanda et al (2015) and Verbruggen et al (2000).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Nevertheless, in the present study, a significant decrease in PS was observed when compared with the insignificant changes in IOP. This result suggests that the changes in PS were not related to IOP, which is in agreement with the hypotheses and findings presented by Kanda et al (2015) and Verbruggen et al (2000).…”
Section: Discussionsupporting
confidence: 82%
“…Despite alterations in IOP in several dogs, these changes were insignificant and IOP remained within physiological limits (10-25 mmHg). Our observations are not in agreement with those of Verbruggen et al (2000), where an increase in IOP in four dogs, and a decrease in 10 dogs, 5 min after administration of medetomidine at 0.15 mg/m 2 body surface area (corresponds to approx. 0.005 mg/kg), was reported.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations